DISTINCTIVE FEATURES OF LEARNING MILITARY JARGON IN THE RUSSIAN LANGUAGE - Shodikhonov , Saidazimkhon (Educational Research in Universal Sciences, 2024)
The article studies the concept of “military terminology” in modern Russian. The relevance of the study is due to the widespread use of military terminology in the media and the rapid advancement of weapons technology. The aim of our research is to study the features of military terminology in modern Russian. The research methods are: the study of scientific literature on the topic, the analysis and the classification. The article distinguishes between the concepts of “military vocabulary” and “military terminology”, defining military terminology as a significant part of military vocabulary. The article explores the problem of studying military terminology in a historical context and analyzes various modern approaches to the classification of military terms concluding that these classifications have a number of shortcomings.